Mixed Adenoneuroendocrine Carcinoma of the Ampulla of Vater - Gabriel Carneiro Fernandes Fonsêca; Marcelo Gonçalves Sousa; Rômulo Gioia Santos Júnior; Gabriela Albuquerque Batista de Araújo; Marcelo Moura Linhares (Archives of Clinical Gastroenterology - Peertechz Publications, 2019)
Introduction: In 2010, World Health Organization defined mixed adeno-neuroendocrine carcinoma as rare tumor with two malignant components: neuroendocrine and adenocarcinomas. A rare mixed adenoneuroendocrine carcinoma of the ampulla of Vater was diagnosticated in this report.  Methods: Diagnosis, surgery and follow-up performed at the Surgical Clinic Service of the Lauro Wanderley University Hospital, from November 2017 to March 2019. Authorized by the patient and approved by the Ethics and Research Committee.  Results: in the current english literature there are only 22 published cases until now. Ampullary carcinoma has been sub classified into 4 categories based on the exact location and such location has distinct prognostic factors. There are three types of morphology according to the distribution of the exocrine and endocrine component: amphicrine, mixed and collision. The mixed type is the most common and present in this case. Diagnosis before the surgery is difficult due to the predominance of non-specific symptoms and because the rarity of the tumor. The surgery is the first line therapy and, after radical resection, adjuvant therapy must be considered, focusing on the more aggressive histology type.  Conclusion: Periampullarys mixed adenoneuroendocrine carcinoma are infrequent tumors, diagnosed after resection and immunohistochemical analysis. There isn't standardization in the management of this disease yet. It is necessary to publish the reported cases for the development of treatments.